Remote Robotic Technology in Minimally Invasive Spinal Surgery: A Comprehensive Literature Review - Aliasghar Karimi; Pegah Pedramfard; Habib Zakeri; Behnam Rahnama; Mohammad Radmehr; Saba Moalemi; Leala Montazeri (International Journal of Telemedicine and Applications)
Telerobotic spinal surgery (TSS) has emerged as a transformative approach for spinal interventions that combines robotics and telecommunication to enable remote surgery with enhanced precision and accessibility. This technology can potentially address the challenges of complex spinal conditions by providing minimally invasive solutions and delivering specialized surgical expertise across geographical boundaries. However, technical complexities related to communication and latency, haptic feedback, and system integration need to be addressed. Ethical and regulatory considerations also require careful navigation. Despite these challenges, the limited number of available clinical studies demonstrates the feasibility and efficacy of TSS, particularly with the use of 5G technology. Further research and clinical trials are needed to fully evaluate and validate the outcomes and effectiveness of TSS. With ongoing efforts in research and development, TSS has the potential to revolutionize spine surgery and improve patient care. In this review, we present the role and the challenges of TSS in spinal surgery.